Figurative Language In Song Lyric “Take Me To Your Heart” By MLTR (Conference on English Language Teaching, 2023)
The material object of this paper is one of the songs sung by a band from Denmark, namely Michael Learns to Rock entitled "Take Me to Your Heart" which was released in 2004. Many of the song lyrics use literal language and are easy to understand.  But different "Take Me to Your Heart" song is full style of language, like figurative language which is interesting to analyze. Therefore, the formal object of this paper is the theory of figurative language. This research employed the qualitative model. The data showed seven types of figurative language found in the lyrics of this song: two allusions, three hyperboles, one metaphor, one personification, one repetition, one anaphora and one assonance.